Neuronal expression of Mgat1 rescues the shortened life span of Drosophila Mgat11 null mutants and increases life span. - Sarkar, M.; Iliadi, K.G.; Leventis, P.A.; Schachter, H.; Boulianne, G.L. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The enzyme UDP-GlcNAc:alpha3-D-mannoside beta1,2-N-acetylglucosaminyltransferase I (GnT1, encoded by Mgat1) controls the synthesis of paucimannose N-glycans in Drosophila. We have previously reported that null mutations in Drosophila Mgat1 are viable but exhibit defects in locomotion, brain abnormalities, and a severely reduced life span. Here, we show that knockdown of Mgat1 in the central nervous system (CNS) of wild-type flies decreases locomotor activity and life span. This phenotype is similar to that observed in Drosophila Mgat1(1) null mutants, demonstrating that Mgat1 is required in the CNS. We also found that neuronal expression of a wild-type Mgat1 transgene rescued the shortened life span of Mgat1(1) null mutants and resulted in a dramatic 135% increase in mean life span relative to genetically identical controls. Neuronal expression of a wild-type Mgat1 transgene in wild-type flies resulted in a modest 9% increase in mean life span relative to genetically identical controls. In both Mgat1(1) null mutants and wild-type flies, neuronal expression of wild-type Mgat1 transgene resulted in a significant increase in GnT1 activity and resistance to oxidative stress. Whereas dietary restriction is not absolutely essential for the increased life span, it plays a role in the process. Interestingly, we observe a direct correlation between GnT1 activity and mean life span up to a maximum of appropriately 136 days, showing that the ability of GnT1 activity to increase life span is limited. Altogether, these observations suggest that Mgat1-dependent N-glycosylation plays an important role in the control of Drosophila life span.